A sequential game-play modelling on forest-title mortgage loans based on Chinese forester resource and assets valuation - Xu, Lu; Strielkowski, Wadim; Liu, Xijing; Schneider, Nicolas; Zhao, Xin (Frontiers in Ecology and Evolution, 2022)
Forest management has become a critical strategic action because of forests’ diverse role in the nature conservation and bio-economic benefits. Forest-title mortgage loan (hereafter abbreviated as “the loan”) which is one of forest management methods not only transforms the “sleeping” resources of a forester in her/his forest into assets mortgageable for cash, but also plays a key role in alleviating the shortage of funds that a forester might encounter, promoting financial innovations, and protecting forest resources. As such, this paper examines the problem of the low limit placed on this loan in China, and draws the following conclusion from employing the dynamic game method comprising complete information: in the actual mortgage market where banks hold an absolute advantage in issuing mortgage loans to the borrower (whether or not a forester acting as the borrower here applies for this loan from the bank through using an asset-appraisal agency) the amount of loan approved for the forester is going to be lower than the actual market value of the forest-resource assets that the forester owns. At the same time, based on the above conclusion, this paper proposes certain suggestions regarding how to raise the limit of this loan for the forester. These suggestions include proposals pertinent to the governmental policy support, introduction of innovative credit products developed by the banks, as well as the elaboration on how foresters could integrate their forest-resource assets by using cooperatives and launching scaled productions.